Reasons to Be Nervous about Flukicide Discovery. Issue 3 (March 2018) - McVeigh, Paul; McCusker, Paul; Robb, Emily; Wells, Duncan; Gardiner, Erica; Mousley, Angela; Marks, Nikki J.; Maule, Aaron G.
Abstract : The majority of anthelmintics dysregulate neuromuscular function, a fact most prominent for drugs against nematode parasites. In contrast to the strong knowledge base for nematode neurobiology, resource and tool deficits have prevented similar advances in flatworm parasites since those driven by bioimaging, immunocytochemistry, and neuropeptide biochemistry 20–30 years ago. However, recent developments are encouraging a renaissance in liver fluke neurobiology that can now support flukicide discovery. Emerging data promote neuromuscular signalling components, and especially G protein-coupled receptors (GPCRs), as next-generation targets. Here, we summarise these data and expose some of the new opportunities to accelerate progress towards GPCR-targeted flukicides for Fasciola hepatica . Highlights: Most existing anthelmintics modulate ion channels on helminth excitable membranes, leading to the disruption of neuromuscular function. GPCRs are targets for more than 30% of the drugs used in human medicine, but only one anthelmintic (emodepside) is known to have a GPCR-directed mode of action. GPCRs transduce signals from the majority of flatworm neurotransmitters, and have essential functions in the control of motility and reproduction. Molecular validations of GPCRs have been performed in Schistosoma mansoni and Schmidtea mediterranea where extensive sequence datasets and functional genomic tools are available. Fasciola hepatica is now a platform for functional neurobiology, benefitting from a sequenced genome, transcriptome datasets, RNAi methodology, functional assays, and efficient in vitro maintenance methods. More GPCRs have been described in the F. hepatica genome than in any other helminth parasite.